The book of fructans - TOKSOY ÖNER, EBRU (Elsevier Science, Oxford/Amsterdam, 2023)
After more than 30 years, The Book of Fructans represents the first and most comprehensive coverage of fructans generated by pioneer glycoscientists from the field. It outlines the fundamentals of all fructan types, their terminology, chemical and structural-functional features, biosynthetic enzymes that make and break them, their presence and possible roles in nature, their evolutionary aspects and their microbial, enzymatic, and plant-based production. Additional sections cover the applications of fructans, specifically, the agro/chemical and biomedical applications, health, pharmaceutical and cosmetic applications, fructans in food and feed, fructan nanotechnology, the immunomodulatory and antiviral effects of fructans and the perspectives for fructans in circular economies and sustainable societies. Intended for scientists, entrepreneurs, academicians and students working in related fields, this book will be a useful resource for all who wish to learn more about these extraordinary carbohydrates.
Keywords: Biyomedikal Mühendisliği; Gıda Mühendisliği; Yaşam Bilimleri; Temel Bilimler; Mühendislik ve Teknoloji; Biomedical Engineering; Food Engineering; Life Sciences; Natural Sciences; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Tarım Bilimleri; Mühendislik; Doğa Bilimleri Genel; GIDA BİLİMİ VE TEKNOLOJİSİ; ÇOK DİSİPLİNLİ BİLİMLER; MÜHENDİSLİK, BİYOMEDİKAL; Agriculture & Environment Sciences (AGE); Engineering, Computing & Technology (ENG); Natural Sciences (SCI); Life Sciences (LIFE); AGRICULTURAL SCIENCES; ENGINEERING; NATURAL SCIENCES, GENERAL; FOOD SCIENCE & TECHNOLOGY; MULTIDISCIPLINARY SCIENCES; ENGINEERING, BIOMEDICAL; Biyomedikal mühendisliği; Biyomühendislik; Yemek bilimi; Multidisipliner; Fizik Bilimleri; Bioengineering; Food Science; Multidisciplinary; Physical Sciences